Sarawak Invention, Innovation & Design Expo (SIIDEx ) 2016: "empowerment through invention, innovation & design (IID) engagement" - Ling, Siew Ching (Universiti Teknologi MARA, Sarawak, 2016)
SIIDex 2016 aimed to nurture the culture of invention, innovation and design among the participants by providing them a platform to compete and showcase their products. It also aimed to identify potential products for commercialisation and to offer an opportunity to promote business cooperation between the academics and the relevant agencies and industries. Besides this, it also aimed to promote science, technology, engineering and mathematics (STEM) among school students.